Cholecyst-jejunostomy for palliative surgery. (February 2021) - Kogo, Hideki; Takasaki, Hideaki; Sakata, Yoshinori; Nakamura, Yoshiharu; Yoshida, Hiroshi
Highlights: Many cases of unresectable cancer that cause obstructive jaundice require treatment. Biliary reconstruction can be difficult to perform safely and quickly due to many factors. Cholecyst-jejunostomy may be completed within 10 min. Cholecyst-jejunostomy is an appropriate palliative surgery. Abstract: Introduction and importance: Many cases of unresectable cancer that cause obstructive jaundice require treatment. Depending on the patient's condition in these cases, surgery may be performed to treat jaundice. The main goal of palliative surgery is to improve the quality of life. Therefore, palliative surgery for obstructive jaundice must be performed safely and quickly. Case presentation: This case presents a 45-year-old man with fever and back pain who was diagnosed with pancreatic head cancer and multiple liver metastases. Chemotherapy was initiated; however, during the course of treatment, the patient developed hemorrhage from pancreatic cancer that had invaded the duodenum caused hematemesis and melena. Therefore, the chemotherapy could not be continued. Because the patient also developed obstructive jaundice and cholangitis, a gastrojejunostomy and cholecyst-jejunostomy was performed. The surgery was successful; however, the cancer continued to progress, and patient died 31 days after surgery. Clinical discussion: Biliary reconstruction can be difficult to perform safely and quickly due to many factors. This study shows that cholecyst-jejunostomy is effective for patients with end-stage cancer. In the long term, cholecyst-jejunostomy is not suitable for biliary reconstruction due to the possibility of bile congestion and cholecystitis. However, this easy and quick procedure is well indicated for emergency patients with a short life expectancy. Conclusion: As an easy and quick procedure for emergency patients with a short life expectancy, jejunal anastomosis of the gallbladder is an appropriate palliative surgery that is indicated for jaundice treatment.